ปัญหาและทางแก้ปัญหาสำหรับระบบบัญชีของวัดไทยในกรุงเทพมหานคร - ชัดตา รัตนานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The thesis aims to study the accounting practices, accounting problems and internal controls of Thai Buddhist temples It Bangkok, including the rules, regulations and related information of Department of Religion, Ministry of Education about accounting requirements. Data collection employed in-depth interview and a questionnaire survey as a research methodology. Both descriptive and inferential statistics (Chi-Square Test) were employed to explain the data and test hypotheses of the study.The analysis pointed out that accounting practices and systems of the most of Thai Buddhist temples in Bangkok were inappropriate as required by general accounting practices and systems and lack of internal controls, especially it expense and fixed asset systems. Most accountants were inexperience and incapable of accounting. It addition, accounting practices and systems did not provide segregation of duty which may cause to fraud in the systems. The study recommended proper accounting practices and systems for different sizes of temples for better internal controls. Moreover, the study described a chart of accounting, account codes, forms, financial reports and document flows of important cycles for reasonable internal controls. Finally, internal auditing for better efficiency of internal controls of Thai Buddhist temples was also provided